2023
DOI: 10.1155/2023/1481114
|View full text |Cite
|
Sign up to set email alerts
|

The Immunoregulatory Effect of Aconite Treatment on H22 Tumor‐Bearing Mice via Modulating Adaptive Immunity and Natural Killer‐Related Immunity

Abstract: Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer and, in its advanced stages, has a 5-year survival rate of only 3% to 5%. Despite novel mechanisms and treatments being uncovered over the past few years, effective strategies for HCC are currently limited. Previous studies have proven that aconite can suppress tumor growth and progression and prevent the recurrence and metastasis of multiple cancers, but the underlying molecular mechanisms are largely unknown. In this study, differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…In the Chinese pharmacopoeia, the recommended dosage of Fuzi is 3–15 g, while in ~51.02% of clinical prescriptions, the dosages of Fuzi were actually far beyond this recommended dose [ 10 ]. Especially for certain patients who might tolerate Fuzi, to gain more effectiveness, the amount of Fuzi could reach as high as 500 g, and strikingly, no severe toxicities were observed in these Fuzi-tolerant patients [ 11 ]. Similar to digoxin and warfarin, Fuzi also demonstrates a rapid transition from onset to poisoning; even worse, the toxic dosage of Fuzi is unpredictable due to individualized response sensitivities [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the Chinese pharmacopoeia, the recommended dosage of Fuzi is 3–15 g, while in ~51.02% of clinical prescriptions, the dosages of Fuzi were actually far beyond this recommended dose [ 10 ]. Especially for certain patients who might tolerate Fuzi, to gain more effectiveness, the amount of Fuzi could reach as high as 500 g, and strikingly, no severe toxicities were observed in these Fuzi-tolerant patients [ 11 ]. Similar to digoxin and warfarin, Fuzi also demonstrates a rapid transition from onset to poisoning; even worse, the toxic dosage of Fuzi is unpredictable due to individualized response sensitivities [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is demonstrated that single dose extract of A . carmichaelii could modulating adaptive immunity and natural killer-related immunity in mice [ 13 ].…”
Section: Introductionmentioning
confidence: 99%